I wanna be your girl. 3 - Takase, Umi (Ink Pop, 2026)
Being in love with your best friend is hard enough, but being a good friend can be even harder. Hime and Akira aren't speaking after an argument; both want to apologize, but they need to come to terms with what being a girl means for each of them. Can these childhood friends find a way to understand each other, or will this be the end? A boy's interest in Hime caused Akira to feel upset and jealous, and the two best friends haven't spoken in weeks. Although they both want to make up, they realize this problem runs deeper than a crush paying attention to someone else. It has to do with him seeing Hime as a girl, and not Akira. Akira is jealous that no one thinks twice about Hime being a girl, while Hime herself is grossed out that a boy might see her as nothing but a girl. The two are left to question their relationships with their gender and with each other. Can they find a way to accept each other and make up?